Analisis Pengaruh Penambahan Berat Badan, Kadar Hemoglobin, Dan Riwayat Penyakit Ibu Selama Hamil Dengan Berat Bayi Lahir Pada Kondisi Berat Bayi Lahir Rendah (BBLR) (Study Observasi di RSIA Fauziyah Tulungagung) - Ratna Kholidati (Akademi Keperawatan Dharma Husada Kediri, 2018)
Low Birth Weight (LBW) is a health problem that is often experienced in most societies characterized by birth weight less than 2500 grams. The occurrence of LBW is basically related to the lack of nutritional fulfillment during the mother's pregnancy and this is related to many factors and more mainstay on family economy problem so that the fulfillment of food consumption need is less. This study aims to analyze the effect of weight gain, hemoglobin level, and history of maternal disease during pregnancy with birth weight in low birth weight (LBW). This type of research is analytical through surveys using observation. Observation is done by using a mother's status card or medical record file. Samples in this research are all babies born in Maternal and Fauziyah Hospital Tulungagung in March 2016 as many as 30 babies. Measurement of variables in this study using Likert scale. The sampling technique uses saturated sampling. Data were analyzed by using simple linear regression analysis. The results showed for the hypothesis of self-influence seen from thitung between maternal weight gain during pregnancy (X1), hemoglobin (X2), history of disease (X3) with t table, there are variables unrelated signified with BBLR (Y ) that is the addition of mother's weight during pregnancy (X1), hemoglobin level (X2). As for the dominant factor that affects LBW (Y) is a history of disease (X3). It can be concluded that a history of maternal illness in pregnancy affects the placenta, which causes a decrease in blood flow to the placenta resulting in a lack of oxygen supply and foodstuffs required by the fetus, leading to fetal growth disorders. Therefore it is necessary to Improve health services and more functioning of infrastructure available in the health.